Determinants of Employee Innovative Work Behavior - Rahmat, Erwan; Sugiarto, Agus; Dwiatmadja, Christantius; Sunarto, Hari (Journal of Ecohumanism, 2024)
The objective of this study is to examine the direct and indirect effects of resilience, transformational leadership, competence, and religious attitudes on innovative work behavior. The data were collected using a questionnaire. The population in this study was 1491 employees. A total of 579 employees participated were subjected to statistical analysis using Partial Least Square-Structural Equation Modeling (PLS-SEM). The findings indicate that the resilience, transformational leadership, and competence have a direct effect on the innovative work behaviour. Similarly, the competence and transformational leadership are also found to have a direct effect on the resilience. However, the religious attitudes have no direct effect on either transformational leadership or resilience. Further, the resilience plays a mediating role in the indirect effect of competence and transformational leadership on the innovative work behavior. In contrast, the resilience fails to mediate the indirect effect between religious attitudes and innovative work behavior. These empirical findings highlight the significant influence of determinants of innovative work behavior.